Tuntutan Kerja dan Dukungan Sosial Rekan Kerja terhadap Presenteeism Guru: Perspektif Job Demands-Resources - Paulus Budi Santosa; Iranita Hervi Mahardiyani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Presenteeism is believed to be a prevalent condition among teachers, driven by high job demands and limited support in the workplace. This study aimed to examine the relationship between job demands and coworker social support with presenteeism among teachers. Participants were selected using quota sampling, involving 42 teachers drawn from a population of 72. Data were collected through three scales measuring presenteeism, job demands, and coworker social support, all of which had been tested for validity and reliability. Multiple regression analysis using SPSS revealed that (1) job demands and coworker social support together were significantly associated with presenteeism (R = 0.639; p = 0.001); (2) job demands had a significant negative relationship with presenteeism (r = -0.587; p = 0.001); and (3) coworker social support had a significant positive relationship with presenteeism (r = 0.537; p = 0.001). These findings suggest that strong collegial bonds among teachers may actually encourage attendance even when unwell, shaped by the collectivist work culture characteristic of Indonesian educational environments.